2013
DOI: 10.1097/ta.0b013e31828cc9a0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing clinical predictors of deep venous thrombosis versus pulmonary embolus after severe injury

Abstract: Background The traditional paradigm is that deep venous thrombosis (DVT) and pulmonary embolus (PE) are different temporal phases of a single disease process, most often labeled as the composite endpoint venous thromboembolism (VTE). However, we theorize that after severe blunt injury, DVT and PE may represent independent thrombotic entities rather than different stages of a single pathophysiologic process and therefore exhibit different clinical risk factor profiles. Methods We examined a large, multi-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Although Golden et al [23] did not provide explicit regularity conditions and a detailed analysis of their proposed general class of GIMTs, Golden et al [23] introduced key formal definitions, provided an informal discussion of relevant theoretical results, and reported the results of a comprehensive simulation study of a realistic epidemiological analysis problem using logistic regression for six new GIMTs that exhibited appealing level and power performance. This approach for the detection of model misspecification has now been used in observational and randomized controlled trial studies [7][8][9][10].…”
Section: Recent Developments In Information Matrix Test Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although Golden et al [23] did not provide explicit regularity conditions and a detailed analysis of their proposed general class of GIMTs, Golden et al [23] introduced key formal definitions, provided an informal discussion of relevant theoretical results, and reported the results of a comprehensive simulation study of a realistic epidemiological analysis problem using logistic regression for six new GIMTs that exhibited appealing level and power performance. This approach for the detection of model misspecification has now been used in observational and randomized controlled trial studies [7][8][9][10].…”
Section: Recent Developments In Information Matrix Test Theorymentioning
confidence: 99%
“…For example, in health economics, estimates of the impact of clinical treatments [3,4], care systems [5], and health policy interventions on health outcomes [6] are dependent on the underlying assumption that the model to be tested is correctly specified. Further, model misspecification testing is essential for statistical analysis of randomized control trials [7,8] and observational studies [9,10]. For these reasons, this paper introduces a unified framework for identifying, classifying, and developing a wide range of specification tests.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major pathophysiologic disturbances shown to be predictive of increased morbidity and mortality after TBI is acute traumatic coagulopathy, with reported incidences ranges from 10%–97.5% [25]. After this immediate hypocoagulable state, a subacute hypercoagulable state develops with the incidence of deep vein thrombosis ranging from 1.8%–44% in major trauma patients [68]. More specifically, the presence of head injury is predictive of an increased risk for thrombotic events [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have rightly pointed out their limitation of not mentioning the severity, site, and nature of trauma as all these have serious implications on the chances of VTE development. Brakenridge et al .,[ 5 ] in their study of 1822 posttraumatic patients, have shown that the site and severity of the injury does matter. Severe thoracic trauma has shown to be significantly associated with the risk of development of PE.…”
mentioning
confidence: 99%